Supporting the emotional needs of young people in care: a qualitative study of foster carer perspectives - Elizabeth Elliott; Rachel M Hiller; Emily Rutter-Eley (BMJ Open)
Objectives Young people who have been removed from their family home and placed in care have often experienced maltreatment and there is well-developed evidence of poor psychological outcomes. Once in care, foster carers often become the adult who provides day-to-day support, yet we know little about how they provide this support or the challenges to and facilitators of promoting better quality carer–child relationships. The aim of this study was to understand how carers support the emotional needs of the young people in their care and their views on barriers and opportunities for support.Design and participants Participants were 21 UK foster carers, recruited from a local authority in England. They were predominantly female (86%), aged 42–65 years old and ranged from those who were relatively new to the profession (<12 months’ experience) to those with over 30 years of experience as a carer. We ran three qualitative focus groups to gather in-depth information about their views on supporting their foster children’s emotional well-being. Participants also completed short questionnaires about their training experiences and sense of competence.Results Only half of the sample strongly endorsed feeling competent in managing the emotional needs of their foster children. While all had completed extensive training, especially on attachment, diagnosis-specific training for mental health problems (eg, trauma-related distress, depression) was less common. Thematic analysis showed consistent themes around the significant barriers carers faced navigating social care and mental health systems, and mixed views around the best way to support young people, particularly those with complex mental health needs and in relation to reminders of their early experiences.Conclusions Findings have important implications for practice and policy around carer training and support, as well as for how services support the mental health needs of young people in care.